Contriving local orthopaedic oncology database: IIUM experience using filemaker pro - Goh, Kian Liang; Sharifudin, Mohd Ariff; Mohamed Amin, Mohamed Azril (2016)
Objectives: To evaluate the efficacy of creating and maintaining Orthopaedic oncology database using Filemaker Pro in the absence of centralised data collection system.